Stress Coping Strategies of Teenage Students at Islamic Boarding School in Probolinggo Regency - Dalilah Rafiq El Imamah; Erdi Istiadji; Erwin Nur Rif'ah (Psychospiritual: Journal of Trends in Islamic Psychological Research, 2025)
Islamic boarding schools offer more intensive education than regular schools so that they can put pressure on students, especially teenagers. The aim of this research is to describe stress management strategies for teenage students at the Nurul Jadid Islamic Boarding School. Data analysis was carried out through transcription, reduction, presentation, inference and review. The stress coping strategies used by the informants include problem-focused coping, self-control, instrumental social support, emotional coping, and religiosity. It is recommended that Islamic boarding schools implement psychological counseling programs to help school administrators and students choose effective coping strategies and manage stress. We We hope that future researchers can apply the same theory to different objects or adapt other theories.